Entre sables et pierres : s’alimenter et boire dans les villages néolithiques d’une zone refuge saharienne de Mauritanie sud-orientale - Sylvie Amblard-Pison (Afriques)
In South-Eastern Mauritania, the cliffs of Tichitt and Oualata have constituted a refuge area abundantly occupied between the beginning of the IIIth millennium BC and that AD, thanks to their water supply. Hundreds of villages with stony walls were built by people living of gathering, hunting, breeding and agriculture. Fetching water, production and harvest of food, their preservation, have led to a very specific organization of the society. Meals were prepared in the compounds by means of ustensils shaped in the local raw materials. Architectural, material and artistic remains testify of the circulation of foodstuffs and of the transmission of the know-how throughout these cliffs. Some areas of the villages seem to have been privileged exchanges places of market type. All of these elements reveal the dynamics and the adaptation of these Neolithic societies in front of vital imperatives which are drinking and eating.